LANDASAN SOSIAL BUDAYA DAN PERKEMBANGAN ILMU PENGETAHUAN DALAM PENGEMBANGAN KURIKULUM - Rosni, Rosni (Inspiratif Pendidikan, 2017)
Abstract: Education basically interacts educative interaction between educator and learner. The purpose of these educational interactions to realize the aspects of the curriculum that apply leads to the achievement of educational goals that have been formulated. Educational interactions are also strongly influenced by the environment, where educational activities occur. The same is said by Oliva in his book Developing the Curriculum, that the Curriculum is an educational tool that directly represents education in addressing community challenges. Community challenges can be categorized in various levels such as national, local, and nearby (regional). These challenges are not arrise just but reconstructed by a group of people and generally legalized by decision makers. Then the curriculum can be considered as the heart of education. That is, educational activities between educators and learners is strongly influenced by the contents that exist in the krikulum. So that in the absence of curriculum as if educational activity is not possible.